2019
DOI: 10.23918/ijsses.v6i2p64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Reading and Rhyming Poetry on Reading Fluency

Abstract: This study tested two instructional methods meant to improve elementary students' automaticity, phonemic awareness, oral fluency, and reading comprehension. Twelve 1 st grade students received either repeated reading or rhyming poetry instruction. A matched group design was used, and then a single subject analysis was employed to determine if either of the methods was associated with improvements in students' reading achievement, oral reading fluency, and attitudes towards reading. Findings indicated that stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…By reading and writing poetry, students receive multifaceted support in their literacy development, thus it is vital that the reading and writing of the genre is occurring regularly and in reciprocity with each other. By reading poems aloud, performing poetry, and reciting their own original poems, students develop oral language and fluency (Certo, 2018;Rasinksi et al, 2016;Zavala & Cuevas, 2019). In fact, Rasinksi et al (2016) found evidence supporting the genre and its ability to "improve the foundational reading outcomes (word recognition accuracy, automatic, and prosody) for students, especially for those who struggle in achieving success in reading achievement due to a lack of foundational competencies" (p. 173).…”
Section: A Case For Reading and Writing Poetrymentioning
confidence: 99%
See 2 more Smart Citations
“…By reading and writing poetry, students receive multifaceted support in their literacy development, thus it is vital that the reading and writing of the genre is occurring regularly and in reciprocity with each other. By reading poems aloud, performing poetry, and reciting their own original poems, students develop oral language and fluency (Certo, 2018;Rasinksi et al, 2016;Zavala & Cuevas, 2019). In fact, Rasinksi et al (2016) found evidence supporting the genre and its ability to "improve the foundational reading outcomes (word recognition accuracy, automatic, and prosody) for students, especially for those who struggle in achieving success in reading achievement due to a lack of foundational competencies" (p. 173).…”
Section: A Case For Reading and Writing Poetrymentioning
confidence: 99%
“…The genre of poetry is the most suitable genre for playing with words because it is “the most amenable to creative and playful exploitation of the potentialities of language” (Myhill, 2013, p. 49). As a result, the genre of poetry positively impacts multiple aspects of a child's literacy development, including foundational skills (Harper, 2011; Rasinksi et al., 2016; Zavala & Cuevas, 2019), composition and craft (Vanderwater, 2018), and comprehension (Rasinksi et al., 2016; Zavala & Cuevas, 2019). The creativity and playfulness that exists within the genre is inviting all learners.…”
Section: A Case For Reading and Writing Poetrymentioning
confidence: 99%
See 1 more Smart Citation